Identification of low frequency oscillation modes in large transmission systems - Jorge Guillermo Calderón-Guizar; Miguel Ramírez-González; Rafael Castellanos-Bustamante (Revista Facultad de Ingeniería Universidad de Antioquia, 2017)
There is a typical dynamical performance associated with every system. Oscillations are phenomena inherent to dynamical systems and the analysis of such phenomena is a fundamental issue for understanding the dynamical behavior of a particular system. Knowledge of the system natural modes, frequencies and its associated damping ratio, provide valuable information regarding the system performance after being subjected to a disturbance. Due to the operational requirements, topological changes in the transmission network of the electrical power systems are quite common. This causes modification in both frequency and damping values of the natural system modes. In the past, normal changes in the operating condition have kicked up undamped power oscillations in the Mexican system, thus assessing the damping of critical oscillation modes of the system is of utmost importance. This paper reports on the application of modal analysis and time domain simulations for computing and tracking the most dominant low frequency oscillations, also known as inter-area modes, in the Mexican power system under different operating conditions. As a result, the most influential system variables on the low frequency oscillations have been identified.